Sittig's handbook of toxic and hazardous chemicals and carcinogens, Volume 1: A-D - Pohanish, Richard P. (William Andrew, Applied Science Publishers, 2017)
Sittig's Handbook of Toxic and Hazardous Chemicals and Carcinogens, Seventh Edition, has proven to be a reliable, accessible, must-have reference on hazardous materials for over thirty years. This updated and revised seventh edition is the most comprehensive listing of the hazardous chemicals commonly used, transported, and regulated in industry and the workplace. Information is the most vital resource anyone can have when dealing with potential hazardous substance accidents, spillages, fires, or acts of terror. It is also essential for the safe day-to-day operation of chemical processes and environmental protection. Sittig's Handbook provides extensive data for over 2,200 chemicals in a uniform format, enabling fast and accurate decisions in any situation. The chemicals are presented alphabetically and classified as a carcinogen, hazardous substance, hazardous waste, or toxic pollutant. This new edition contains expanded and reviewed information for each chemical listed (including chemicals classified as WMD) and has been updated to keep pace with world events, standards, and regulations. This seventh edition includes over 100 new records, and every single record has been checked and updated as necessary.Enables readers to quickly and reliably find the chemical they are looking for, with a full range of synonyms for each chemical, including trade names and CAS indexFeatures relevant data for the US and EU included throughout, along with the essential chemical hazard information applicable worldwideProvides a trusted source of information for first-line responders (emergency services), industry, logistics companies, scientists, and environmental protection organizationsContains expanded information for each chemical listed (including chemicals classified as WMD) and has been updated to keep pace with world events, standards, and regulations